2017
DOI: 10.1039/c6ra27634b
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature solution synthesis of CuO/Cu2O nanostructures for enhanced photocatalytic activity with added H2O2: synergistic effect and mechanism insight

Abstract: The morphological transformation was observed after photodegradation and the as-grown samples exhibited relatively good durability as photocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…The main limitation of their application results from not good photostability, which is very important issue for oxidative photocatalytic systems. Generally, Cu 2 O possesses higher photocatalytic activity than CuO for degradation of organic compounds [75,76]. Although CuO has much smaller band gap than Cu 2 O, and thus is able to absorb more vis photons, the positions of CB and VB for CuO are insufficient to catalyze the production of hydroxyl and superoxide radicals, which are primary initiators for the photocatalytic oxidation of organic compounds [75].…”
Section: Cuo-tio2 Heterojunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitation of their application results from not good photostability, which is very important issue for oxidative photocatalytic systems. Generally, Cu 2 O possesses higher photocatalytic activity than CuO for degradation of organic compounds [75,76]. Although CuO has much smaller band gap than Cu 2 O, and thus is able to absorb more vis photons, the positions of CB and VB for CuO are insufficient to catalyze the production of hydroxyl and superoxide radicals, which are primary initiators for the photocatalytic oxidation of organic compounds [75].…”
Section: Cuo-tio2 Heterojunctionmentioning
confidence: 99%
“…Although CuO has much smaller band gap than Cu 2 O, and thus is able to absorb more vis photons, the positions of CB and VB for CuO are insufficient to catalyze the production of hydroxyl and superoxide radicals, which are primary initiators for the photocatalytic oxidation of organic compounds [75]. Deng et al found that combined CuO/Cu 2 O nanostructures can be efficient photocatalysts for the photodegradation of organic compounds and possess better resistance against photocorrosion [76]. They proposed that the co-existence of CuO could inhibit the photocorrosion of Cu 2 O, and furthermore the CuO/Cu 2 O system can be more photocatalytically efficient than single CuO or Cu 2 O.…”
Section: Cuo-tio2 Heterojunctionmentioning
confidence: 99%
“…Octahedron morphology can be clearly distinguished for Cu 2 O nanoparticles with average edge length to be about 5–80 nm. Previously, many researchers have been synthesized octahedral Cu 2 O crystals in different ways . For example, Ho et al prepared octahedral nanoparticles of Cu 2 O based on the reduction of copper nitrate in Triton X‐100 with average edge length from 45 to 95 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Wet peroxide oxidation (with and without catalysts), Fenton and photo-Fenton oxidations, and sono-, electro-, or photo-chemical reactions are some of the main processes where H 2 O 2 is employed for water and wastewater treatment [12][13][14][15][16][17][18][19]. Particularly, H 2 O 2 is widely used in photocatalytic water treatment because the addition or even in situ generation of H 2 O 2 has been established as a promoter of the degradation of pollutants [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%